Twelve lectures on domestic science - Elder, Mary Amy (My University, 1908)
Introduction: Lecture I Methods of Cookery. Man, undoubtedly lived on raw food at one time, but since cooking has been resorted to for so long, he has lost the power of digesting raw food of many kinds. The purposes of cooking are – 1. To develop certain flavors in the food which act as stimulants to the appetite.
Citation: Elder, Mary Amy. Twelve lectures on domestic science. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Home Economics; Education; Lectures; Graduating theses; Senior theses; Theses